Constitutions and social networks - Ana Mauleon; Nils Roehl; Vincent Vannetelbosch (Fondazione Eni Enrico Mattei (FEEM), 2015)
The objective of the paper is to analyze the formation of social networks where individuals are allowed to engage in several groups at the same time. These group structures are interpreted here as social networks. Each group is supposed to have specific rules or constitutions governing which members may join or leave it. Given these constitutions, we consider a social network to be stable if no group is modified any more. We provide requirements on constitutions and players' preferences under which stable social networks are induced for sure. Furthermore, by embedding many-to-many matchings into our setting, we apply our model to job markets with labor unions. To some extent the unions may provide job guarantees and, therefore, have influence on the stability of the job market.
Keywords: C72; C78; D85; 330; Social Networks; Constitutions; Stability; Many-to-Many Matchings